The translocator protein ligands as mitochondrial functional modulators for the potential anti-Alzheimer agents - TaeHun Kim; Mohammad N. Morshed; Ashwini M. Londhe; Ji W. Lim; Ha E. Lee; Suengmok Cho; Sung J. Cho; Hayoung Hwang; Sang M. Lim; Jae Y. Lee; Jiyoun Lee; Ae N. Pae (Journal of Enzyme Inhibition and Medicinal Chemistry, 2021)
Small molecule modulators of mitochondrial function have been attracted much attention in recent years due to their potential therapeutic applications for neurodegenerative diseases. The mitochondrial translocator protein (TSPO) is a promising target for such compounds, given its involvement in the formation of the mitochondrial permeability transition pore in response to mitochondrial stress. In this study, we performed a ligand-based pharmacophore design and virtual screening, and identified a potent hit compound, 7 (VH34) as a TSPO ligand. After validating its biological activity against amyloid-β (Aβ) induced mitochondrial dysfunction and in acute and transgenic Alzheimer’s disease (AD) model mice, we developed a library of analogs, and we found two most active compounds, 31 and 44, which restored the mitochondrial membrane potential, ATP production, and cell viability under Aβ-induced mitochondrial toxicity. These compounds recovered learning and memory function in acute AD model mice with improved pharmacokinetic properties.